Educação musical e o Transtorno do Espectro Autista - Oliveira, Fábio Júnior Soares de (My University, 2024)
The autism spectrum disorder is a neurodevelopmental disorder that generates significant deficits in communication and social interaction. In regards to musical education with students within the spectrum, the teachers' difficulties range from lack of professional and structural preparation to difficulties in finding support in the scientific literature. Based on this principle, this project aims to review the literature on what has been produced for the last 7 years in the field of music education for students diagnosed with Autism Spectrum Disorder (ASD). Therefore, a survey was carried out in the Annals of Brazilian Association of Music Education's (ABEM) Regional Meetings and National Congresses, between the years 2015 and 2021, focusing on experience reports, activities proposals and auxiliary materials. As a result, socialization and inclusion practices that can contribute to both musical and non-musical skills were identified. [resumo fornecido pelo autor]
O transtorno do espectro autista é um distúrbio no desenvolvimento neurológico que gera déficits significativos na comunicação e interação social. No que se refere à educação musical com alunos no espectro, as dificuldades dos professores vão de falta de preparo profissional e estrutural até dificuldade de amparo na literatura científica. Partindo deste princípio, este projeto tem por objetivo uma revisão bibliográfica acerca do que se tem produzido nos últimos 7 anos no âmbito da educação musical para alunos com diagnóstico de Transtorno do Espectro do Autismo (TEA). Para tanto foi realizado um levantamento nos Anais dos Encontros Regionais e Congressos Nacionais da Associação Brasileira de Educação Musical (ABEM), entre os anos de 2015 a 2021, com foco em relatos de experiência, propostas de atividades e materiais auxiliares. Como resultados foram identificadas práticas de socialização e inclusão que podem contribuir tanto em habilidades musicais quanto em não-musicais. [resumo fornecido pelo autor]
Keywords: Música - Instrução e estudo; Transtornos do espectro autista; Autismo - Música; Educação inclusiva